2009
DOI: 10.1590/s0103-50532009000200017
|View full text |Cite
|
Sign up to set email alerts
|

Green and roasted arabica coffees differentiated by ripeness, process and cup quality via electrospray ionization mass spectrometry fingerprinting

Abstract: A habilidade da técnica de espectrometria de massas com infusão direta e ionização por eletronebulização (IES-EM), nos modos de íons positivos e negativos, foi avaliada na diferenciação de cafés Arábica verdes e torrados e com diferentes estágios de amadurecimento (verde, maduro e passado), processo pós-colheita (seco, úmido e semi-úmido) e cafés classificados por prova de xícara. No modo negativo, a análise dos cafés verdes mostrou que os íons correspondentes aos ácidos graxos e ácidos clorogênicos desprotona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 28 publications
3
41
0
4
Order By: Relevance
“…Identification of the ions was done comparing the m/z values and MS/MS data obtained by ESI FT-ICR MS in the negative-ion mode with a homemade library of coffee compounds based on literature search (Alonso-Salces, Guillou, & Berrueta, 2009;Amorim et al, 2009;Clarke & Vitzthum, 2001;Clifford, Johnston, Knight, & Kuhnert, 2003;Jaiswal & Kuhnert, 2010) and standards. We considered a match between the experimental m/z value and the theoretical m/z value from our library when the mass error was <3 ppm.…”
Section: Mass Spectrometry and Ion Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of the ions was done comparing the m/z values and MS/MS data obtained by ESI FT-ICR MS in the negative-ion mode with a homemade library of coffee compounds based on literature search (Alonso-Salces, Guillou, & Berrueta, 2009;Amorim et al, 2009;Clarke & Vitzthum, 2001;Clifford, Johnston, Knight, & Kuhnert, 2003;Jaiswal & Kuhnert, 2010) and standards. We considered a match between the experimental m/z value and the theoretical m/z value from our library when the mass error was <3 ppm.…”
Section: Mass Spectrometry and Ion Identificationmentioning
confidence: 99%
“…Coffee quality is a demanding analytical task because the genetic background of the plants, associated with agronomic practices and environmental conditions e such as climate, soil type, and altitude e can affect the final chemical composition of the grain (Amorim et al, 2009;Leroy et al, 2006;Vaast, Bertrand, Perriot, Guyot, & Génard, 2006). Furthermore, the genetic variability has been reported to contribute to coffee acidity, sugars, chlorogenic acids, lipids, and caffeine (Guerrero, Suárez, & Moreno, 2001;Kitzberger et al, 2010;Ky et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…An electrospray ionization mass spectrometry fingerprinting was developed for green and roasted coffees for differentiating them by different stages of ripeness (green, ripe, and overripe), post-harvesting process (dry, wet, and semi-wet) and cup quality. 51 The quality of coffee was also investigated by the determination of fatty acid profile 52 and by evaluating the prediction of sensory properties by solid phase microextraction-gas chromatography and partial least squares. 53 In the first work it was shown that the fatty acid methyl ester composition could not be used to detect corn adulteration in commercial coffees.…”
Section: Foodsmentioning
confidence: 99%
“…Direct infusion ESI‐MS requires no or little sample preparation yielding almost instantaneous information about the composition of a given sample 13. Some recent studies have reported the employment of direct infusion ESI‐MS to obtain fingerprints of samples as diverse as rum and Brazilian artisan cachaça,14 essential oils,13 whisky,15 beer,16 vegetable oils,11, 17 coffee,18 wine,19 biodiesel,20 media used for in vitro production of bovine embryos,21 grape juices,22 perfume,23 genetically modified soybeans,24 and snake venoms 25. In conjunction with chemometric methods, such as principal component analysis (PCA) and hierarchical clustering analysis (HCA) used to treat the MS data, ESI‐MS has been successfully applied to classify, for instance, samples of vegetable oils10 and Brazilian artisan cachaça aged in different wood casks 26…”
mentioning
confidence: 99%